External evaluation in Roald Dahl’s The BFG - Joanna Deborah (Universitas Islam Sultan Agung, 2020)
There have been several significant changes in children’s literature in the past few decades; one of them is the change in the narative style. Roald Dahl is one of the most prominent authors of children’s literature that displays this particular change in his works. Dahl is known to utilize a creative narrative style in his works, and this is also seen in one of his children’s novels discussed in this research: The BFG (1982). This research thus aims at analysing one part of the narrative structure called external evaluation which shows the function of narrator in the story as well as the effects of the use of such narrative style on children as the target readers. Using Labov’s theory of narative structure and Genette’s theory of narratology, the results of the analysis shows that Dahl utilizes the function of narrator in the external evaluations to help children as his target readers to get a better understanding of the story as well as to build a close connection with them, resulting in the more enjoyable reading experience for the children.